WALI MUJBIR DALAM PERSPEKTIF PEMIKIRAN KH. HUSEIN MUHAMMAD - Khoiri, Miftakhul (TAHKIM, 2024)
The Koran's comments regarding marriage are explicit in many verses. There are around 104 verses, including the vocabulary of marriage which is repeated 23 times and the word zauwj which is repeated 80 times. An in-depth review of all the marriage scriptures lays out the five principles of marriage. First, the principle of mawadah wa rahmah. Second, the principle of monogamy. Third, the principle of mu'āsyarah bil-ma'rūf (polite communication). Fourth, the principle of mutual enhancement and protection in interpersonal relationships and sexuality. Fifth, the principle of determining partners for prospective brides and grooms. Society believes that women do not have full rights in matters of marriage, so choosing a partner must be left to their parents. Selection of a partner as one of the principles of marriage often conflicts with the right of ijbar held by the guardian. This ultimately became the focus in Islam, a woman's right to decide on a partner is the sole right of her parents, not the right to decide on a partner. The claim that has developed so far is that mujbir guardians are parents who claim that their children were married off by their parents' choice, or better known as "forced marriage". This paper aims to analyze the use of KH Husein Muhammad's socio-historical approach in the form of the mashlahah concept in Fiqh/Usul Fiqh with the aim of reaching a middle point between the differences. Keywords: marriage, guardian mujbir, legal istbat